Effect of Serum Level of Vitamin D on External Apical Root Resorption in Maxillary Anterior Teeth in Patients under Fixed Orthodontic Treatment - Fatemeh Azizi; Nasim Karami; Amin Golshah; Mohammad Moslem Imani; Roya Safari-Faramani (International Journal of Dentistry)
Introduction. This study aimed to assess the effect of serum level of vitamin D on external apical root resorption (EARR) in maxillary anterior teeth in patients under fixed orthodontic treatment. Materials and Methods. This retrospective cohort was conducted on patients under fixed orthodontic treatment who were between 12 to 30 years of age. All patients underwent the same treatment technique by the same orthodontist using a 0.022 MBT system. EARR in maxillary anterior teeth was evaluated on pre- and postoperative panoramic radiographs. Blood samples were also collected from patients, and their serum level of vitamin D was measured after the completion of treatment. Data were analyzed by independent t-test and Chi-square test (alpha = 0.05). Results. A reduction in root length was noted in all patients, which was significant (P<0.0001); 75% of patients showed EARR in at least one maxillary incisor. EARR had no significant correlation with the serum level of vitamin D (P=0.423). Conclusions. Serum level of vitamin D had no significant correlation with the occurrence of EARR. However, the high prevalence of EARR calls for measures to minimize it.